Screening of Glyphosate Herbicide-Degrading Rhizosphere Bacteria from Chili Pepper (Capsicum frutescent L.) Farm Soil - Lailatun Nikmah, Alvi; Lisdiana, Lisa (LenteraBio : Berkala Ilmiah Biologi, 2023)
Research on the utilization of rhizosphere bacteria in degrading glyphosate herbicides is important because the excessive use of glyphosate herbicides can cause residues accumulation in the soil and contaminate crops, one of which is chili pepper (Capsicum frutescent L.). The purpose of this study was to obtain and characterize rhizosphere bacterial isolates that have the potential to degrade glyphosate herbicides from chili pepper farm soil samples in Sumberagung village, Blitar. Screening and isolation were done using MSM (Mineral Salt Medium) media containing glyphosate herbicide (25, 50, 100 ppm). Characterization in the form of colony and cell morphological characteristics, motility test, and catalase test were analyzed descriptive qualitatively. The bacterial isolation obtained fourteen isolates that were able to grow on MSM media with 25 and 50 ppm glyphosate. On MSM media with 50 ppm glyphosate there were seven isolates that could grow. The results of characterization of these isolates showed diverse characteristics. Based on these results, it can be concluded that the seven isolates that grow on MSM media with 50 ppm glyphosate have higher potential as biodegraders of glyphosate herbicides. These isolates need to be identified so that can be utilized to help the implementation of bioremediation in farm soil.